Genome Sequence Analysis Reveals Selection Signatures in Endangered Trypanotolerant West African Muturu Cattle - Tijjani, Abdulfatai; Utsunomiya, Yuri Tani; Ezekwe, Arinze G.; Nashiru, Oyekanmi; Hanotte, Olivier (Frontiers in Genetics, 2019)
Like most other West African Bos taurus, the shorthorn Muturu is under threat of replacement or crossbreeding with zebu. Their populations are now reduced to a few hundred breeding individuals and they are considered endangered. So far, the genetic variation and genetic basis of the trypanotolerant Muturu environmental adaptation have not been assessed. Here, we present the genome-wide candidate positive selection signatures of Muturu following iHS and Rsb signatures of selection analysis. We compared the results in Muturu with ones obtained in N’Dama, a West African longhorn trypanotolerant taurine, and to two European taurine (Holstein and Jersey). The results reveal candidate signatures of selection regions in Muturu including genes linked to the innate (e.g. TRIM10, TRIM15, TRIM40, TRIM26) and the adaptive (e.g. JSP.1, BOLA-DQA2, BOLA-DQA5, BOLA-DRB3, BLA-DQB) immune responses. The most significant regions are identified on BTA 23 at the bovine major histocompatibility complex (MHC) (iHS analysis) and on BTA 12 overlapping genes including for heat tolerance (e.g. INTS6) (Rsb analysis). Other candidate selected regions include genes related to growth traits/stature (e.g. GHR and GHRHR), coat colour (e.g. MITF and KIT), feed efficiency (e.g. ZRANB3 and MAP3K5) and reproduction (e.g. RFX2, SRY, LAP3 and GPX5). Genes under common signatures of selection regions with N’Dama, including for adaptive immunity and heat tolerance, suggest shared mechanisms of adaptation to environmental challenges for these two West African taurine cattle. Interestingly, out of the 242,910 SNPs identified within the candidate selected regions in Muturu, 917 are missense SNPs (0.4%), with an unequal distribution across 273 genes. 15 of these genes including RBBP8, NID1, TEX15, LAMA3, TRIM40 and OR12D3 containing a total of 220 missense variants, each between 11 and 32. Our results, while providing insights into the candidate genes under selection in Muturu, are paving the way to the identification of genes and their polymorphisms linked to the unique tropical adaptive traits of the West Africa taurine, including trypanotolerance.